Recent Progress in Base Metal Catalyzed (Transfer) Hydrogenative Couplings of Carbonyls with π-Unsaturated Compounds - Zheng, Yan-Long; Luan, Yu-Xin; Ye, Mengchun (Synlett, 2016)
Catalytic hydrogenative coupling of carbonyls with π-unsaturated compounds employing hydrogen gas or H donors as terminal reductants is an attractive method for C–C bond formation. Herein, we give a brief review on its development and highlight recent advances on the use of base metal catalysts, such as nickel and iron.1 Introduction2 Noble Metal Catalyzed (Transfer) Hydrogenative Couplings of Carbonyls with π-Unsaturated Compounds3 Nickel-Catalyzed Transfer Hydrogenative Couplings of Paraformaldehyde with π-Unsaturated Compounds4 Iron-Catalyzed Transfer Hydrogenative Couplings of Carbonyls with π-Unsaturated Compounds5 Conclusion
Keywords: iron catalysis; unactivated aldehydes; simple alkenes; hydrogen transfer; hydrogenative coupling